Effects of an electronic medication management system on pharmacists' work in a paediatric hospital. (10th July 2019) - Baysari, Melissa T.; Hardie, Rae‐Anne; Barclay, Peter; Westbrook, Johanna I.
Abstract: Background: Many studies have explored the effect of electronic medication management systems (EMMS) on doctors' and nurses' work, but few have focused specifically on pharmacists' work. Aim: This study examined how implementation of a commercial EMMS affected the work of pharmacists in an Australian paediatric hospital. In particular, the study investigated whether any pharmacy tasks changed or were eliminated, or whether new tasks emerged following EMMS introduction. Methods: Two rounds of semistructured interviews with pharmacists, one 4 months and the other 1 year after EMMS implementation, were conducted. In total, 17 pharmacists were interviewed, comprising inpatient, outpatient and oncology pharmacists, as well as pharmacy managers. Results: EMMS implementation eliminated a small number of tasks, changed some tasks and created many new work tasks for pharmacists. These new tasks included helping doctors and nurses to use the EMMS, duplicated data entry and the review of additional information. Pharmacists held the view that their workload had increased and that additional pharmacists were necessary to cope with the new work requirements associated with the EMMS. Some problems were perceived to be the result of implementation of a US‐designed EMMS that did not fully support Australian pharmacy workflows. Conclusion: Implementation of an EMMS in a paediatric hospital affected pharmacists' work in a variety of ways, predominately by introducing new tasks. Anticipating how workflows will change with EMMS implementation is challenging. Undertaking regular reviews of workflow and planning for an increased burden on pharmacy staff is likely to improve the transition from paper to electronic medication management.